HEREDITARY DOMAIN - IRAWATI (NIM: 20106012), RIANA
The aim of this work is to prove the equivalence of various characterizations of a hereditary domain. Which are the equivalence between Invertible Ideal Domain (IID), Ideal Factorization Domain (IFD), One dimensional Unique Ideal Factorization Domain (UIFD), Dedekind domain and hereditary domain. Let A be a domain. Then A is hereditary if and only if A is a IID if and only if A is a IFD if and only if A is a one dimension UIFD if and only if A is Dedekind domain